Illustrated men drawing and rendering the male fashion figure - O'Neal, Lamont (Bloomsbury Visual Arts, a trademark of Bloomsbury Publishing Plc, 2023)
"The ultimate guide to drawing and rendering the male fashion figure"--Provided by publisher.